Systematic numerical analysis of the hydraulic parameters responsible for critical flows in anthropogenically modified mountain channels for flood analysis and mitigation - C. Hauer; L. Schmalfuss; U. Pulg (Journal of Flood Risk Management)
Abstract The damage potential in river systems due to flood flows has increased as a result of the increased infrastructure and population growth along river corridors, frequently accompanied by an incomplete understanding of flood safety and the impact of climate change. In particular, so‐called catastrophic flood events in alpine areas are generally accompanied by massive channel beds and floodplain erosion with a higher damage potential than inundation only. It has been recently shown that critical flow conditions might be an important driver of uncontrolled erosion and channel avulsion in terms of extraordinary flood events. A systematic analysis, however, of the parameters driving critical flow conditions is lacking. Thus, the aim of this study was to conduct a systematic numerical evaluation of the hydraulic parameters responsible for critical flows in steep mountain channels as a baseline study for future improved flood impact assessment and mitigation measure design. The systematic analysis of standardized river bathymetries revealed that channel slope, roughness and river widening impose decreasing influences on alpine rivers to produce critical flow conditions. However, there is a risk that due to human interventions, altering the natural slope–roughness relationship to increase the discharge capacity for flood safety might promote critical conditions. These findings should be considered in future hydraulic engineering practice.